Deutsches oder globales Wirtschaftswunder? Zur Ökonomie der Gründerjahre - Jan-Otmar Hesse (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2025)
– Though long de-mystified by economic history literature, the idea of a German "economic miracle" of the 1950s occasionally shows up in popular discourse, propelled by political motivation. The article starts with a brief summary of older arguments for reconstruction as opposed to a structural break having caused economic recovery. It then addresses the more recent discussion on the continuation of the economic order after 1945. Both debates, however, have neglected the international dimension of Germany's spectacular growth episode. The article therefore asks, if indicators of the structural transformation to a market economy can be found on the global level.
Keywords: N14; N44; N74; 330; Germany; Economic Miracle; Bretton Woods System; Economic Order